Asuhan Keperawatan Dengan Inhalasi Aromaterapi Lavender Untuk Menurunkan Nyeri Pada Anak Di Ruang Lili Infeksi RSUD Arifin Achmad Pekanbaru - Ruthmita Septiani; Syeptri Agiani Putri; Rosdiana Rosdiana (Yayasan Jompa Research and Development, 2023)
Pain is a defense mechanism for the body that arises when tissue is being damaged which causes the individual to react by moving the pain stimulus. Handling that can be done to treat pain is by using pharmacological techniques (medical drugs) and non-pharmacological. Non-pharmacologically pain can be treated using aromatherapy, deep breathing, distraction, hypnotherapy, guided imagery techniques and messages. Giving lavender aromatherapy is considered effective in reducing pain because it gives a feeling of comfort and relaxation so that it can reduce the range of pain. The method used is a case study using 2 respondents who were treated in the Lili room at Arifin Achmad Hospital, Riau Province, which aims to see differences in the patient's pain scale before and after being given lavender aromatherapy inhalation. The criteria for this observation patient are patients with moderate pain scale. This nursing care is carried out directly to child I and child II. The intervention was given for 3 days, the results showed a good development of the patient's condition, there was a decrease in the pain scale in children. Based on the results of the application of nursing care to children with pain, giving lavender aromatherapy inhalation has been proven to reduce the pain scale felt by patients. so it is suggested to pediatric nurses to be able to practice giving lavender aromatherapy inhalation in the management of patients with pain nursing problems.